A domino reaction of 3-chlorochromones with aminoheterocycles. Synthesis of pyrazolopyridines and benzofuropyridines and their optical and ecto-5′-nucleotidase inhibitory effects. Issue 5 (5th January 2018) - Miliutina, Mariia; Janke, Julia; Hassan, Sidra; Zaib, Sumera; Iqbal, Jamshed; Lecka, Joanna; Sévigny, Jean; Villinger, Alexander; Friedrich, Aleksej; Lochbrunner, Stefan; Langer, Peter
Abstract : Biologically active fused pyridines were prepared by a new domino reaction. Abstract : A new and efficient domino reaction of 3-chlorochromones with electron-rich aminoheterocycles was developed which allows for a convenient synthesis of a variety of pyrazolo[3, 4- b ]pyridines, pyrrolo[2, 3- b ]pyridines, pyrido[2, 3- d ]pyrimidines and benzofuro[3, 2- b ]pyridines. The products exhibit strong fluorescence. In addition, they exhibit significant ecto-5′-nucleotidase inhibition properties and cytotoxic behavior.